Crystalline metal-organic frameworks (MOFs): synthesis, structure and function - Dey, Chandan; Kundu, Tanay; Biswal, Bishnu P.; Mallick, Arijit; Banerjee, Rahul (Acta Crystallographica Section B-Structural Science, 2014)
Metal-organic frameworks (MOFs) are a class of hybrid network supramolecular solid materials comprised of organized organic linkers and metal cations. They can display enormously high surface areas with tunable pore size and functionality, and can be used as hosts for a range of guest molecules. Since their discovery, MOFs have experienced widespread exploration for their applications in gas storage, drug delivery and sensing. This article covers general and modern synthetic strategies to prepare MOFs, and discusses their structural diversity and properties with respect to application perspectives.